Comparative expression analysis of rice and arabidopsis peroxiredoxin genes suggests conserved or diversified roles between the two species and leads to the identification of tandemly duplicated rice peroxiredoxin genes differentially expressed in seeds - Gho, Yun-Shil; Park, Sun-A; Kim, Sung-Ruyl; Chandran, Anil Kumar Nalini; An, Gynheung; Jung, Ki-Hong (Springer, 2017)
# Background